An investigation on RYO/MYO tobacco characteristics and smoke emissions as a function of cigarette design elements - Nikolov Nikolay; Nikolova Violeta; Petrova Todorka; Bozhinova Radka; Dyulgerski Yovko; Popova Venelina (BIO Web of Conferences)
Fine-cut tobacco blends for hand-made cigarettes (RYO/MYO) represent a significant part of the contemporary tobacco market in Bulgaria and worldwide. Their popularity is due mainly to the affordable price and the option to adjust cigarette design to smoker’s preferences. The objective of the current study was to determine the main physical and chemical characteristics of different brands of RYO/MYO tobacco available on the national market, and to follow the impact of cigarette design elements on the levels of smoke emissions. Four variants of laboratory cigarettes with varying design parameters (length, diameter, paper type and permeability, tobacco weight) using five tobacco brands were analyzed. High share of long strands (over 80%) was found for all blends, and the cut width was below 0.40 mm. Tobacco moisture content was higher than that in sold cigarettes. The nicotine content varied 1.98-2.50%, reducing sugars – 11.30-17.00%, ash – 11.03-13.04%, Cl – 0.65-1.09%, K – 2.58-2.88%. One and the same blend produced different levels of nicotine, tar and CO depending on cigarette design variation, and the reduction of tobacco weight by just 0.07 g resulted in over 15% decrease in smoke emissions. In most of the blends and cigarette variants smoke emissions exceeded significantly the limitations applied for commercial cigarettes.